Drugs for the Treatment of Chronic Hand Eczema: Successes and Key Challenges - Dubin C; Del Duca E; Guttman-Yassky E (Dove Medical Press, 2020)
Celina Dubin,1 Ester Del Duca,1,2 Emma Guttman-Yassky1,3 1Department of Dermatology, Laboratory of Inflammatory Skin Diseases, Icahn School of Medicine at Mount Sinai, New York, NY, USA; 2Department of Dermatology, University of Magna Graecia, Catanzaro, Italy; 3Laboratory for Investigative Dermatology, The Rockefeller University, New York, NY, USACorrespondence: Emma Guttman-YasskyDepartment of Dermatology, Laboratory of Inflammatory Skin Diseases, Icahn School of Medicine at Mount Sinai, 5 E. 98th Street, New York, NY 10029, USATel +1 212-241-9728Fax +1 212-876-8961Email Emma.Guttman@mountsinai.orgAbstract: Chronic hand eczema (CHE) is a common and burdensome inflammatory skin condition seen in up to 10% of the population, more often in high-risk occupational workers. Topical therapeutics comprise the standard of care, but up to 65% of cases do not resolve after treatment, and moderate-to-severe cases are often resistant to topical therapeutics and require systemic options instead. To date, there are no systemic therapeutics approved to treat CHE in the United States, but several drugs are under investigation as potential treatments for CHE. The primary focus of this review is on the novel therapeutics, topical and systemic, that are under investigation in recently completed or currently ongoing trials. This review also briefly outlines the existing treatments utilized for CHE, often with limited success or extensive adverse effects. CHE represents a major challenge for physicians and patients alike, and efforts to improve the minimally invasive diagnostic tools and treatment paradigms are ongoing. In the near future, CHE patients may benefit from new topical and systemic therapeutics that specifically target abnormally expressed immune markers.Keywords: AFX5931, chronic hand eczema, delgocitinib, dupilumab, gusacitinib, roflumilast